The Charter of the Rights of the Family in the Context of Theology of Law - Gałkowski, Tomasz 1967- (2014)
The author in his article analyses the content of the Charter of the Rights of the Family in theological perspective. First, he emphasises the specificity of theology of law, whose reference point are the persons creating a relation in the obligation aspect (proper relation). This relation is subject of the new understanding in the light of the details of Revelation. They constitute hermeneutical categories for theology of law in the Charter of the Rights of the Family. Next, the author analyses its particular points from the angle of these categories. In his conclusions he emhasises that opening oneself to faith gives the possibility of fuller understanding of the things created by the human being (including law) and for the human being.
Keywords: Familienrecht; Familie; Rechtstheologie; Charter of the Rights of the Family; teology of law